Histone Deacetylase Inhibitor MS-275 Alleviates Postoperative Cognitive Dysfunction in Rats by Inhibiting Hippocampal Neuroinflammation. (1st October 2019) - Wu, Yang; Dou, Juan; Wan, Xing; Leng, Yan; Liu, Xuke; Chen, Lili; Shen, Qianni; Zhao, Bo; Meng, Qingtao; Hou, Jiabao
Abstract: Neuroinflammation in the hippocampus plays essential roles in postoperative cognitive dysfunction (POCD). Histone deacetylases (HDACs) have recently been identified as key regulators of neuroinflammation. MS-275, an inhibitor of HDAC, has been reported to have neuroprotective effects. Therefore, the present study aimed to test the hypothesis that pretreatment with MS-275 prevents POCD by inhibiting neuroinflammation in rats. In this study, anesthesia/surgery impaired cognition, demonstrated by an increase escape latency and reduction in the number of platform crossings in Morris water maze (MWM) trials, through activating microglia neuroinflammation and decreasing PSD-95 expression. However, pretreatment with MS-275 attenuated postoperative cognitive impairment severity. Furthermore, pretreatment with MS-275 decreased activated microglia levels and increased PSD95 protein expression in the hippocampus. Pretreatment with MS-275 reduced NF-κB-p65 protein expression and nuclear accumulation as well as the neuroinflammatory response (production of proinflammatory cytokines including TNF-α and IL-1β) in the hippocampus. Additionally, MS-275 reduced HDAC2 expression and HDAC activity in the hippocampus, which were enhanced in vehicle-treated rats. These results suggest that MS-275 alleviates postoperative cognitive dysfunction by reducing neuroinflammation in the hippocampus of rats via HDAC inhibition. Highlights: HDAC2 was sensitive to anesthesia/surgery-induced postoperative cognitive dysfunction than HDAC1 or HDAC3. MS-275 reduced HDAC2 expression and HDAC activity, which were enhanced by anesthesia/surgery. Administration of MS-275 suppressed NF-κB-p65 protein expression and nuclear accumulation as well as neuroinflammatory responses. MS-275 attenuated postoperative cognitive impairment severity.